Interações geoecológicas nas planícies de marés do litoral centro-sul sergipano - Santos, Geisedrielly Castro dos (2016)
The estuarine dynamics in the state of Sergipe favored the formation of tidal plains in all the river mouths, in areas sheltered from the mechanical action of the waves and that are influenced by the tidal regime, totaling an estimated area of about 260 km². The aim of this thesis was to analyze the evolution of the tidal plains on the south-central coast of Sergipe. The research used as methodological procedures, guided by the method of Geoecology of Landscapes: acquisition, processing of satellite images and aerial photographs, creation of the shapes and construction of thematic mappings; Quantification of the area of the subject classes; Fieldwork and data interpretation. The analyzes showed that the energy signatures of the tidal plains that make up the study area are similar, except for the influence of the natural tensor: fluviomarine dynamics and anthropogenic tensors acting on the study area. The evolutionary analysis of the tidal plain between the neighborhoods 13 de Julho and Jardins (Aracaju / SE) showed that the reduction of mangrove vegetation was due to sedimentation promoted by the erosion of the sandy crown of Coroa do Meio and due to the low availability of nutrients in the environmental system; The evolutionary dynamics of the tidal plains at the mouth of the Vaza Barris (Itaporanga D'Ajuda / SE) revealed that the long-term tide plains are in stability, and the short-term tides are in instability with a tendency to reduce by fluvial erosion And low availability of nutrients; The evolutionary analysis of the Piauí / Real river mouths (Estância / SE) revealed the occurrence of long - term tidal plains that suffered severe losses of mangrove vegetation due to fluvial erosion, with total loss of vegetation in this area of 44,000 m². It was concluded from the results that all the tidal plains located in the analyzed mouths have a general tendency to the loss of mangrove vegetation both by fluvial-influenced influence (Vaza Barris) and by fluviomarine and anthropogenic influence (Piauí / Real and Sergipe). The proposed geoecological study serves as an instrument to assist in the environmental planning of the Sergipe coastal zone with regard to the rearrangement of human occupations. These actions should occur in compliance with the variability of the back lines associated with river mouths, and towards the conservation of environmental systems, such as survival security for the communities that depend on mangroves, and for maintaining biodiversity that is reflected in Supply for society as a whole.